Pengaruh Harga dan Kualitas Produk Terhahap Keputusan Pembelian Chatime Dan Koi The di Kota Bandung - Pasaribu, Samuel Sahat Maruli; Hidayat, Agus Maolana (Universitas Sam Ratulangi, 2023)
The purpose of this study is to determine the effect of price and product quality on the purchase decision of Chatime and Koi The in Bandung City. The type of research used is quantitative methods. The sampling technique uses non-probability sampling with a type of purposive sampling. A total of 100 questionnaires were collected and analyzed using multiple linear regression using SPSS Version 26. The results of the study showed that price and product quality partially or simultaneously had a significant effect on Chatime's purchase decision, while product quality had a significant effect on the purchase decision of Koi The, products while price had no effect. But simultaneously the price and quality of the product have a significant effect on the purchase decision of Koi The in the city of Bandung.